Intellectual Capital in Global Accelerator Programs: An Empirical Analysis of Survival Probabilities in Emerging Countries - Carlos Eduardo Canfield-Rivera; Luis Salvador Mondragón-Sotelo; Joerg Hruby (Ciencias Administrativas Teoría y Praxis)
This research examines the influence of initial Intellectual Capital (IC) on the survival probabilities of new ventures in accelerator programs operating in emerging countries. It confirms the beneficial impact of IC assets on startup survival during the pre-performance phase. While most existing studies focus on advanced economies, this research highlights the significance of IC for startups in emerging markets. Our findings show that IC accumulations, encompassing useful and applicable knowledge, enhance survival prospects even after accounting for potential unobserved heterogeneity and considering both external and internal influences. The study also underscores the critical role of accelerator programs with well-structured curricula, particularly those focusing on specific impact areas, in enhancing startup survival. The wider economic environment significantly influences survival probabilities, suggesting the need for future research on the operational dynamics of startups and accelerators across different country groups. This research opens avenues for further studies on the mediating and moderating effects of IC components on performance, particularly in the context of human capital and financial constraints, thereby addressing gaps in the literature and expanding our understanding of startup survival determinants in emerging economies.